2016
DOI: 10.1259/bjr.20160512
|View full text |Cite
|
Sign up to set email alerts
|

Image quality assessment of single-shot turbo spin echo diffusion-weighted imaging with parallel imaging technique: a phantom study

Abstract: Objective: This study aimed to evaluate the image quality and apparent diffusion coefficient (ADC) values of single-shot turbo spin echo (TSE) diffusion-weighted (DW) images obtained using a parallel imaging (PI) technique. Methods: All measurements were performed on a 3.0-T whole-body MRI system and 32-channel phased-array coil. Signal-to-noise ratio (SNR) and ADC values were measured with a DW imaging (DWI) phantom comprising granulated sugar and agar. The SNRs were calculated using a subtraction method and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 29 publications
3
26
0
1
Order By: Relevance
“…Furthermore, reduced image blurring in the phase-encoding direction was observed as AF increased in both CS and SENSE, although the increase in AF led to an increase in image noise. This is consistent with the results of a recent study [11] and could be explained by the fact that the higher AF reduces the shot duration, which causes image blurring owing to T 2 decay in the phase-encoding direction. Considering the above-mentioned findings, TSE-DWI using CS maintains geometric accuracy, provides less variation in ADC values, and reduces scanning time in comparison with TSE-DWI using SENSE.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, reduced image blurring in the phase-encoding direction was observed as AF increased in both CS and SENSE, although the increase in AF led to an increase in image noise. This is consistent with the results of a recent study [11] and could be explained by the fact that the higher AF reduces the shot duration, which causes image blurring owing to T 2 decay in the phase-encoding direction. Considering the above-mentioned findings, TSE-DWI using CS maintains geometric accuracy, provides less variation in ADC values, and reduces scanning time in comparison with TSE-DWI using SENSE.…”
Section: Discussionsupporting
confidence: 93%
“…Our study also demonstrated the variability of ADC values and geometric accuracy measurements obtained from TSE-DWI using SENSE and CS. The reproducibility of the ADC values obtained with TSE-DWI was similar to that reported in a recent study, regardless of whether SENSE or CS were used [11]. In addition, the CV values of geometric accuracy measurements were good with both CS and SENSE.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous study reported that the SNR of TSE-DWI was lower than that of EPI-DWI owing to multiple RF refocusing pulses; 21 however, the image quality of TSE-DWI has been recently improved by using the modulus averaging method, short RF pulses, and SENSE. 22,32 Our results are attributable to the high SNR achieved by these factors. To calculate the SNR, ROIs were placed in the areas with homogeneous subcutaneous fat in both TSE-DWI and EPI-DWI (b = 850 s/mm 2 ).…”
Section: Discussionmentioning
confidence: 70%
“…4 Recently, parallel imaging technique and higher signal-to-noise ratio (SNR) at 3T improved these issues with single-shot TSE-DWI. 1,4 The utility of TSE-DWI has been reported in evaluations of middle ear cholesteatoma, orbital and neck lesions, TECHNICAL NOTE study was assessment of the image quality and artifacts with 4-point scales. The secondary endpoint was comparison of ADC, as described in detail below.…”
Section: Introductionmentioning
confidence: 99%